Worker Protection Standard: Owner and Immediate Family Exemption - Frederick M. Fishel; Tatiana Sanchez (EDIS, 2016)
This revised 3-page FAQ fact sheet answers questions about the exemptions for owners and their immediate families in the Worker Protection Standard (WPS). Written by Frederick M. Fishel and Tatiana Sanchez, and published by the Agronomy Department, October 2016.